Organizational pathology : life and death of organizations - Samuel, Yitzhak (London : Routledge, 2017)
"Organizational Pathology draws an extended metaphor that the life cycle of an organization is akin to the biological life cycle. Like all living things, organizations will encounter problems that lead to decline and eventual failure. This work discusses the basic problems and life threatening diseases responsible for organizations' failure and death, including organizational politics, organizational corruption, and organizational crime. The book also contains a critical look at crises and fixations; failure and survival; and processes of disbandment and closure of dying organizations.The consideration of these issues follows a diagnostic model of failure. Yitzhak Samuel argues that if the problems that lead to failure can be predicted or diagnosed early, their severity can be assessed and possible remedies can be implemented to avoid escalating crises. At the very least, an understanding of why and how decline happens can be gained from this analysis. This book offers facts about the causes and consequences of organizational downfall and clues about diagnoses of certain symptoms of abnormal behavior, and how to identify early signs of decline or failure. In order to illustrate these abstract arguments and concepts, Samuel uses various real-life examples of events that have occurred in cross-country contexts. In this way, Organizational Pathology: Life and Death of Organizations should serve a variety of readers.Although primarily intended for students and scholars in the social and behavioral sciences who are familiar with the study and the practice of organizations, this book's informal style makes it easily accessible to a wide range of readers. Just as Samuel's previous book on organizational politics led to new lines of research and theory, this book will encourage similar studies in organizational pathology and institutional malaise."--Provided by publisher.
chapter 1 A Theoretical Framework -- chapter 2 Organizational Fatality -- chapter 3 Failure Prediction Models -- chapter 4 Maladies and Disorders -- chapter 5 The Spiral of Decline -- chapter 6 The Perils of Politics -- chapter 7 Greed and Corruption -- chapter 8 Corporate Crime -- chapter 9 Crises and Fixations -- chapter 10 Failing and Surviving -- chapter 11 Disbandment and Closure -- chapter 12 Lessons Learned.
First published 2010 by Transaction Publishers.
Keywords: Organizational effectiveness